PREFERENSI GENERASI MILENIAL DALAM MENGGUNAKAN E-WALLET DI KOTA DENPASAR - Paramitha, Ni Made Ayu Mila; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022DO - 10.24843/EEB.2022.v11.i05.p07, 2022)
This study aims to empirically test the influence of perceived ease of use, perceived usefulness , and perceived risk on millenial’s interest in e-wallet usage. Technology acceptance model was applied as a theoretical framework to investigate the determinants of e-wallet acceptance. This study used a quantitative approach targeting the millennial’s e-wallet users. Research data were collected through online survey with google form and resulted in 145 respondents’ answers which were then analyzed using SmartPLS. Research findings revealed that risk was not significantly influence millennial’s interest in e-wallet usage. While ease of use and perceived usefulness were found to be significant predictors of e-wallet acceptance among millennials. Perceived ease of use has the greatest influence on e-wallet acceptance compared to other variables. This study offers some practical recommendations for e-wallet providers to better understand millennials preferences and fulfil their expectations.